WETLANDS AND ITS IMPORTANCE : A CASE STUDY OF LOKTAK LAKE IN MANIPUR - Singh, Akoijam Amitkumar (SCHOOL SCIENCE, 2011)
Wetlands are the primary habitat for many flora and fauna. The Loktak lake was designated as “Wetland of International Importance” under Ramsar Convention in 23 March, 1990 due to its rich and unique biodiversity. The present study was undertaken to understand the resource linkage and livelihood options of the surrounding inhabitants of the Loktak lake. The sites chosen for the study included Sendra, Ithing, Thanga II and Karang Islands. The analysis of the socio-economic data collected from the regions shows that a large population of the study area depends upon the resources of the lake for their livelihood (fishery and vegetation for domestic consumption and commercial purposes). On the other hand, the study also shows that most of the inhabitants engaged in fishing lack modern scientific and technical knowhow of fishing which has adverse impacts in the production and efficacy of the whole process. Women of the region were also found to be involved in making fishing-nets for income generation rather than weaving of traditional clothes, which later results in declining of small scale industries. Most of the inhabitants were found to be aware of the importance of the lake in their life and hence would actively support any conservation programme. The findings suggest that proper management of Phum, introduction of modern techniques, sustainable fishing, improved tourism, etc., will take care of most of the problems